Konstruksi Double Plot Twist Dalam Film Horor Sorop (2024): Pendekatan Naratologis Fabula–Syuzhet Dan Struktur Temporal - Paulus Heru Wibowo Kurniawan; Bisma Fabio Santabudi (ARTCHIVE: Indonesian Journal of Visual Arts and Design, 2025)
This study analyzes the use of double plot twist techniques in the narrative structure of the Indonesian horror film Sorop (2024), directed by Upi Avianto. A plot twist is understood as a narrative strategy that disrupts audience expectations and shapes intense emotional experiences. The research employs a qualitative descriptive method with a narratological approach, applying Bordwell’s (1987; 2013) fabula–syuzhet concepts and Pérez’s (2020) temporal structure of plot twists. Data were gathered through repeated viewing of the film’s audiovisual text, mapping of the fabula and syuzhet, three-act segmentation, and identification of the pre-twist, twist moment, and post-twist integration phases. The analysis reveals that Sorop exploits the information gap between the fabula and syuzhet to deliver two main plot twists: first, a cognitive twist revealing Bude Sabah as the true antagonist; second, an affective-symbolic twist that destroys any sense of safety through the continuation of a cyclical curse. This integration not only strengthens suspense on an aesthetic level but also represents cycles of trauma, familial power relations, and the uncanny return. The findings enrich the study of Indonesian film narratology and offer practical insights for filmmakers in crafting complex and manipulative horror narratives.